Sistem Penunjang Keputusan Pilihan Karir Mahasiswa Informatika Di Perusahaan BUMN Menggunakan Metode AHP Berbasis Web - Hetty Rohayani; Rico; Rahmi Handayani; Wella Sandria (LPPM Universitas Adiwangsa Jambi, 2026)
In order to meet the needs of life, work is a very basic field in order to get money to meet the needs of life. With the development of the business world in the era of globalization, the breadth of opportunities and diversity of jobs offered, especially in the field of Information Technology (IT). This situation makes Informatics students of the University of Muhammadiyah Jambi confused in choosing future careers. One method that is relevant and has a consistency value calculation in determining the priority level of criteria is the Analytical Hierarchy Process (AHP) method. This study aims to build a Decision Support System website using the AHP method. The results showed a consistency ratio value of 0.06249 which means less than the consistency ratio value used in the AHP method, which is 0.1, so that the calculation results are valid, and can be used. The final result of this application provides a decision recommendation that BRI is the most ideal state-owned company in the career choice of UMJ Informatics students with a value of (0.544258) followed by PLN (0.239861), Telkom (0.149692) and Pertamina (0.066188). These results are obtained from the calculation of priority criteria and alternatives using the AHP method.